Investigating the Issue of Dyslexic Pupils in the Algerian Classroom - Adda Sekrane, Chifaa (My University, 2022)
The present work aims at investigating the issue of dyslexic pupils in the Algerian classroom. The main question that is raised in this research is whether teachers are aware of their pupils’ language disorders, mainly, dyslexia. The problematic at hand seeks to find out whether teachers are trained to identify and cope with dyslexia in pupils. In order to answer this research question, the requirement of the present investigation urged the employment of a triangular approach which is the mixed method. A structured interview directed to different speech therapists from Relizane was conducted as a data collection tool that was directed to speech therapists from Relizane. Questionnaires were also delivered to middle school teachers. Moreover, an observation coupled with an experiment of verbal behavior were also conducted in the classroom. The targeted participants are teachers from Ameur Ameur Abdelkader middle school in Relizane, and two groups of informants containing respectively 24 and 25 pupils. The whole experiment was based on Skinner’s linguistic approach which is the verbal behavior approach. The findings of this research proved that applying Skinner’s reinforcement theory of motivation in the classroom can be effective to dyslexic pupils. However, teachers are not fully aware of their pupils’ language disorder neither do they adjust and evaluate their teaching method with them because they are not trained enough to identify the issue on their pupils.
Case study: Second Year Middle School Pupils in Ameur Ameur Abdelkader, Relizane
Keywords: Dyslexia; Language Disorder; Reading and Writing Difficulties; Algerian Middle School Classroom; Skinner’s Reinforcement; Theory of Motivation